Value of a statistical life in Argentina: an experiment of declared preferences in the choice of road : Valor de una vida estadística en Argentina: estimación en base a un experimento de preferencias declaradas de elecciones de viaje - Conte Grand, Mariana (2005)
This manuscript is based on a declared preferences pilot survey undertaken at the Buenos Aires-La Plata Highway on December 2004. The survey was designed following a functional fraccional approach with three attribute variables: cost, risk and time. Results based on Logit models show that the value of avoiding a death (or the value of a life) would be approximately 50 Argentinean cents (or 30 if we discard lexicographic behavior). This is similar to results obtained in other similar countries as Chile. In addition, the resulting value of time is approximately 4 Argentinean pesos/hour.